Culture as Politics : Selected Writings of Christopher Caudwell - Caudwell, Christopher, 1907-1937 (Book collections on Project MUSE., 2018)
"Selected essays by Christopher Caudwell, on culture, psychology, and capitalism. Material drawn from Caudwell's previous book, "Illusion and Reality, Studies in a Dying Culture" and his essay, "Heredity and Development.""--